2020
DOI: 10.1007/s13311-020-00871-0
|View full text |Cite
|
Sign up to set email alerts
|

Treating Post-traumatic Stress Disorder with Neuromodulation Therapies: Transcranial Magnetic Stimulation, Transcranial Direct Current Stimulation, and Deep Brain Stimulation

Abstract: Post-traumatic stress disorder (PTSD) is a prevalent and debilitating illness. While standard treatment with pharmacotherapy and psychotherapy may be effective, approximately 20 to 30% of patients remain symptomatic. These individuals experience depression, anxiety, and elevated rates of suicide. For treatment-resistant patients, there is a growing interest in the use of neuromodulation therapies, including transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), and deep brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…In this article, we suggest hypothetical mechanisms for the effects of DBS on memory. We showed that dropout of engram nodes could disrupt memory processes, which might be useful in translating DBS as a treatment for anxiety disorders like PTSD (Gouveia et al, 2020 ). We also showed that dropout of engram nodes could improve memory function and suggested that this happens through increased synaptic function.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we suggest hypothetical mechanisms for the effects of DBS on memory. We showed that dropout of engram nodes could disrupt memory processes, which might be useful in translating DBS as a treatment for anxiety disorders like PTSD (Gouveia et al, 2020 ). We also showed that dropout of engram nodes could improve memory function and suggested that this happens through increased synaptic function.…”
Section: Discussionmentioning
confidence: 99%
“…DMPFC is crucial in the DMN related to self-referential processing and episodic memory ( 41 ). More recently, non-invasive brain stimulation (NIBS) such as repetitive transcranial magnetic stimulation (rTMS) or transcranial direct current stimulation (tDCS) has been shown to alleviate PTSD-associated symptoms ( 43 ). For instance, high frequency stimulation on the right DLPFC has been shown to reduce re-experiencing feelings, avoidance, hyperarousal ( 44 ), related depressive ( 44 , 45 ) and anxiety symptoms ( 44 ), and suicidal ideation ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although DBS has been used routinely to treat depression 47 and obsessivecompulsive disorder 48 and preclinical DBS studies in fear conditioning animal models have suggested its potential use for treatment-resistant PTSD, [49][50][51] very few studies have explored the clinical effect of DBS in PTSD. [52][53][54] About 20% to 30% of PTSD patients do not respond to medications and conventional psychotherapy. 49,51 A recent clinical trial showed that 6 patients with treatment-resistant PTSD experi enced a 30% decrease in clinician-administered PTSD scale scores after bilateral basolateral amygdala highfrequency stimulation.…”
Section: Discussionmentioning
confidence: 99%